Development of a pH-paralleling approach of quantifying six-category pharmaceuticals in surface water using SPE-HPLC-MS/MS - Bing Hong; Shen Yu; Min Zhou; Juan Li; Jing Ding; Yong Niu (Watershed Ecology and the Environment, 2021)
An analytical protocol was developed to quantify six-category pharmaceuticals in surface water under paralleling pHs using a combination of solid phase extraction (SPE) and high-performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS). Of 121 compound standards commercially, 94 compounds were reliably quantified using a paralleling pH combination at 3 and 9 with a sound recovery-rate of 50-150%. The quantified compounds covered 6 categories as 37 antibiotics, 16 central nervous system drugs (CNs), 14 cardiovascular drugs (CVs), 12 endocrine and family planning drugs (EFs), 8 antiparasitic drugs (APs), and 7 non-steroidal anti-inflammatory drugs (NSAIDs). The protocol achieved limits of detection and quantitation in ranges of 0.001–11.9 ng L–1 and 0.003–39.7 ng L–1, respectively. Serial field surface water samples from Jiulong River in Fujian, China were testified using the protocol with 41 quantified compounds of the above-mentioned 6 categories from < LODs to 1,389 ng L−1 (caffeine). The key procedure prior to the SPE is to split filtrate of each surface water sample into two portions, adjusted to pH 3 and 9 separately and both spiked with 0.2 g Na2EDTA.